Treatment-induced neural reorganization in aphasia is language-domain specific: Evidence from a large-scale fMRI study. (February 2023) - Barbieri, Elena; Thompson, Cynthia K.; Higgins, James; Caplan, David; Kiran, Swathi; Rapp, Brenda; Parrish, Todd
Abstract: Studies investigating the effects of language intervention on the re-organization of language networks in chronic aphasia have resulted in mixed findings, likely related to—among other factors—the language function targeted during treatment. The present study investigated the effects of the type of treatment provided on neural reorganization. Seventy individuals with chronic stroke-induced aphasia, recruited from three research laboratories and meeting criteria for agrammatism, anomia or dysgraphia were assigned to either treatment ( N = 51) or control ( N = 19) groups. Participants in the treatment group received 12-weeks of language intervention targeting sentence comprehension/production, naming, or spelling. At baseline and post-testing, all participants performed an fMRI story comprehension task, with blocks of auditorily-presented stories alternated with blocks of reversed speech. Participants in the treatment, but not control, group significantly improved in the treated language domain. FMRI region-of-interest (ROI) analyses, conducted within regions that were either active (or homologous to active) regions in a group of 22 healthy participants on the story comprehension task, revealed a significant increase in activation from pre-to post-treatment in right-hemisphere homologues of these regions for participants in the sentence and spelling, but not naming, treatment groups, not predicted by left-hemisphere lesion size. For the sentence (but not the spelling) treatment group, activation changes within right-hemisphere homologues of language regions were positively associated with changes in measures of verb and sentence comprehension. These findings support previous research pointing to recruitment of right hemisphere tissue as a viable route for language recovery and suggest that sentence-level treatment may promote greater neuroplasticity on naturalistic, language comprehension tasks, compared to word-level treatment.